Dari Dublin ke Ramallah: Analisis Tiga Level Masukan Dalam Pengakuan Irlandia atas Kedaulatan Palestina Pada Tahun 2024 - Bhirawa, Raden Bagus Rusydannu Risysya; Mutmainah, Dian (Universitas Cenderawasih, 2025)
Ireland’s long-standing position as one of EU’s most vocal members of Palestinian rights and statehood took a huge leap when it decided to recognize the state of Palestine on May 2024. However, Ireland is far from being considered an enemy of Israel, as both countries share diplomatic and economic ties for decades. Despite economic threats from Israel and limited support in Europe, Ireland firmly stood by its decision along with Norway and Spain. To understand this decision, Charles W. Kegley & Shannon L. Blanton has laid out a useful framework to analyse inputs contributing to a transnational actor’s foreign policy, which are: global conditions, its internal characteristics, and actor leadership. Using this framework, this article argues that leadership, particularly by Simon Harris and his party, Fine Gael was the key driver, grounded in past policy, diplomatic coordination, and the context of the 2024 early elections. This study concludes that several inputs contribute to this decision, namely; a global uproar against Israel’s military aggression in Gaza post October 7th, an ever-strong pro-Palestine tide in the Irish public, its small-state characteristics, and Simon Harris’ recent ascension to power. KEYWORDS Ireland; Foreign Policy; Palestinian Statehood; Palestine-Israel